A clinical and instrumental study of heart failure in amyloidotic cardiomyopathy. (25th November 2020) - Caponetti, A.G; Longhi, S; Saturi, G; Ponziani, A; Sguazzotti, M; Massa, P; Milandri, A; Salvi, F; Biagini, E; Rapezzi, C; Galie', N; Gagliardi, C
Abstract: Background: Heart failure (HF) is one of the main features of amyloidotic cardiomyopathy (AC) and it is supposed to carry important prognostic implications. Despite the intrinsic etiologic heterogeneity of AC, HF has been mainly attributed to diastolic dysfunction, but the role played by the different amyloid subtypes of AC and by the clinical and hemodynamic factors in the pathophysiology of HF remains unclear. Objectives: We aimed to assess the hemodynamic profile and outcome of patients with or without advanced HF (defined as NYHA class III-IV) at the time of first evaluation in light-chain (AL), hereditary transthyretin-related (h-ATTR) and non-mutant transthyretin-related (wt-ATTR) AC. Methods: Among the 411 patients diagnosed with AC (156 AL, 131 h-ATTR, 124 wt-ATTR) at our Centre between 1990–2019, we analyzed central hemodynamic data, echocardiographic, clinical, ECG details and survival of the whole cohort. Cox regression analysis was used to stratify prognosis. Results: 112 (27%) patients presented advanced HF at first evaluation and frequently showed severe symmetric left ventricle wall thickening (higher values in h-ATTR), non-dilated left ventricle, preserved ejection fraction and pathological global longitudinal strain and/or myocardial contraction fraction. At ECG, a significantly lower QRS voltage was present in advanced HF patients. Hemodynamically, elevated filing pressures on both cardiac sides were present in patients in NYHA III-IV class of the three etiologies. Overall survival at 2 years was 35% for AL, 83% for h-ATTR, 65% for wt-TTR. H-ATTR and wt-TTR were favorable predictors of survival, while reduced cardiac index and elevated filling pressures were indepedently associated with higher mortality. Conclusions: The characterization of hemodynamic profile plays a central role in predicting the natural history of AC, since reduced stroke volume and elevated filling pressures are the best predictors of mortality, reflecting a physiopathological restrictive model of the disease. Conversely, left ventricular ejection fraction is rarely abnormal and it is not a reliable marker of poor prognosis, especially in the early stages of the disease. AL amyloidosis shows the worst outcome probably due to a combination of the underlying illness and light chains cardiotoxicity. Funding Acknowledgement: Type of funding source: None